HUBUNGAN PERHATIAN ORANG TUA PADA PEKERJAAN RUMAH (PR) TERHADAP HASIL BELAJAR MATEMATIKA - Warseno; Muhammad Jainuri; Awatif (Hira Institute, 2026)
This research is motivated by the low mathematical understanding of grade X students of SMA Negeri 3 Merangin in the 2024/2025 academic year, the lack of parental guidance when doing homework, and low student compliance. The aim is to assess the relationship between parental attention to homework and mathematics learning outcomes. The study used a quantitative approach with a correlational method. From a population of 192 students, a sample of 66 students was taken using the Slovin formula and simple random sampling using a randomizer application. Data were obtained through a questionnaire for parental attention and daily test scores for learning outcomes. Normality and linearity tests showed normal and linear data. Analysis used Pearson product moment correlation, t-test, and coefficient of determination. The results showed a significant relationship between parental attention and mathematics achievement (r count 0.2351 > r table 0.2042; t count 1.9350 > t table 1.6690). Parental attention contributed 5.53% to student achievement, while 94.47% was influenced by other factors. These findings emphasize the importance of family support for learning success, and can be a consideration for parents, teachers, and schools to improve the quality of learning and student achievement.